Identification of Streptococcus mutans from Human Dental Plaque and Dental Caries Using 16SrRNA Gene - Flayyih, Adhraa S.; Hassani, Hayfa H.; Wali , Mohammed H. (Iraqi Journal of Science, 2022)
One hundred and sixty samples from saliva and dental plaque were sellected from patients with caries active at ages from (4-65) years from Umm Qasr Primary School and Al-Ameria Specialist Dental Center in Baghdad. 15 isolates belong to Streptococcus mutans were identified by biochemical tests and Vitek 2 compact system while 22 isolates identified by using Polymerase Chain Reaction ﴾PCR﴿ techniques and sequencing of 16SrRNA with 120 bp by using 16SrRNA the result confermed that these isolates were belong to S.mutans.